BRIEF CHARACTERISTIC OF EUROPEAN GENOTYPE TICK-BORNE ENCEPHALITIS VIRUS STRAINS IDENTIFIED IN SIBERIAN REGION - S. E. Tkachev (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
The molecular-genetic analysis of 13 strains of Western genotype TBEV isolated in Western and Eastern Siberia demonstrated two groups of strains differed geneticallyfrom each other and had a high level of E gene sequences homology within each group. Nevertheless, the heterogeneity of biological propertiesfor some strains within a group was observed.